3,4-Diaminopyridine masks the inhibition of noradrenaline release from chick sympathetic neurons via presynaptic alpha 2-adrenoceptors: insights into the role of N- and L-type calcium channels - Dolezal, V; Huang, H Y; Schobert, A; Hertting, G (Brain research, 1996)
We have investigated the participation of the N-type (omega-conotoxin GVIA-sensitive) and L-type (nifedipine-sensitive) calcium channels in the alpha 2-adrenoceptor mediated autoinhibition of the release of [3H]noradrenaline from chick sympathetic neurons in culture. Blockade of 3,4-diaminopyridine-sensitive potassium channels resulted in tetrodotoxin-sensitive and calcium-dependent increase of the release of [3H]noradrenaline evoked by electrical stimulation. Nifedipine attenuated the evoked release under control conditions by 20%, but in the presence of 3,4-diaminopyridine by 51%, while omega-conotoxin decreased the release under control conditions by 87% and in the presence of 3,4-diaminopyridine by only 43%. The L-type calcium channel activator Bay k 8644 increased the evoked release of the transmitter both in the absence and in the presence of 3,4-diaminopyridine. Under control conditions, the alpha 2-adrenoceptor agonist UK 14304 decreased the evoked release by 57% and the alpha 2-adrenoceptor antagonist rauwolscine increased it by 14%. Nifedipine did not prevent this modulation. In the presence of 3,4-diaminopyridine, UK 14304 lost its effect on the release of noradrenaline, but its inhibitory action was restored when nifedipine, but not omega-conotoxin, was added. Changes in the increase of intracellular calcium concentration ([Ca2+]i) evoked by electrical stimulation, measured in the cell processes by microfluorimetry, paralleled the changes in the release of [3H]noradrenaline. Under control conditions, nifedipine attenuated the rise of intracellular calcium by only 16%, while omega-conotoxin did so by 66%. 3,4-Diaminopyridine enhanced the evoked rise of [Ca2+]i; in its presence the rise of intracellular calcium was about equally reduced by nifedipine and omega-conotoxin (by 46 and 36%, respectively). These effects were additive. UK 14304 diminished the peak concentration of [Ca2+]i elicited by the standard electrical stimulation by 31% and rauwolscine antagonised this effect. UK 14304 did not measurably inhibit the stimulation-evoked rise of intraterminal [Ca2+]i in the presence of 3,4-diaminopyridine but it produced an inhibition by 26% if nifedipine had been applied together with 3,4-diaminopyridine. Our observations show that, under control conditions, the stimulated release of [3H]noradrenaline is mainly associated with the opening of N-type channels, while in the presence of 3,4-diaminopyridine the contribution of L-type channels becomes more important. The alpha 2-adrenoceptor stimulation by UK 14304 inhibits the release of [3H]noradrenaline but, in the presence of 3,4-diaminopyridine, the inhibition of release can only be observed if the massive influx through L-type calcium channels is prevented. These data suggest that presynaptic alpha 2-adrenoceptors of chick sympathetic neurons preferentially influence the N-type calcium channels.
Keywords: fluorescenční barviva; Amifampridine; Fluorometry; Neurons; kultivované buňky; fura-2; alfa-2-adrenergní receptory; Receptors, Adrenergic, alpha-2; Brimonidine Tartrate; brimonidin tartarát; receptory presynaptické; Chick Embryo; agonisté adrenergních alfa-receptorů; Fluorescent Dyes; chinoxaliny; Calcium Channels; kuřecí embryo; 4-aminopyridin; fluorometrie; Adrenergic alpha-Agonists; noradrenalin; Cells, Cultured; Quinoxalines; zvířata; Fura-2; Potassium Channels; neurony; draslíkové kanály; elektrická stimulace; sympatický nervový systém; Sympathetic Nervous System; amifampridin; vápníkové kanály; Norepinephrine; 4-Aminopyridine; Electric Stimulation; Receptors, Presynaptic; Animals